POSITIONING OF AUTOMOBILE BRANDS IN YOGYAKARTA MARKET - , Eko Fachruroji, Prof. Dr. Basu Swastha Dhammesta, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this research is to get insight and to analyze the positioning of automobile brands (Toyota, Honda, Suzuki, Nissan, Isuzu, Mitsubishi, Daihatsu, and Hyundai). The positioning of those brands was represented on perceptual mapping by using some multidimensional scaling methods. Six attributes (model, price, machinery performance, fuel consumption, comfort, and feature completeness) are also included as an attempt to get the attribute perceptual mapping which has purpose to describe those brands based on attributes evaluation. What perceptual mapping does is to represent consumer perception, it makes operationally the concept of positioning. This research results two kinds of perceptual mapping which are non-attribute perceptual mapping that based on overall direct judge of similarity, and joint space (stimuli and attribute) perceptual mapping whereas the attribute ratings was required based on derived measures of similarity by using semantic differential attitude scale. Based on what is perceptual mapping resulted in this research, Toyota and Honda were perceived to be similar, it is mean Toyota compete tightly with Honda. Nissan and Daihatsu were perceived to be similar, thereby they are competing strictly. Isuzuâs position is far off from other brands, it can be interpreted that Isuzu has no close competitors. In term of prominent attributes, Suzuki has a large number of attributes attached to it compare to other brands. It is clustered by attribute of model, price, and fuel consumption. Nissan is seen to be associated to feature completeness. Mitsubishi is seen to be reliable in machinery performance. While the others brands such as Toyota, Honda, Daihatsu, Hyundai, and Isuzu seen with no any of prominent attribute attached to them.